Kajian Perilaku Masyarakat Pesisir yang Mengakibatkan Kerusakan Lingkungan di Pantai Mangrove Desa Tanjung Rejo Kecamatan Percut SEI Tuan - Nasution, Aldi Syahputra; Hasibuan, Arini Salsabila; Thoibah, Baldatun; Pratiwi, Dwika Ardelya; Ayenti, Erika; Pratiwi, Khairani Putri; Barus, Maharani Br; Sirait, Salshabila Azzahra; Priyatna, Sekar Harum; Mawaddah, Qisti; Ayu, Delfriana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One of the busiest places is the beach. The beach is where the highest tide meets the mainland. The beach is a rapidly developing tourist destination with strategic potential, including the mangrove beach. The most common environmental problem is waste. The high rate of waste generation will definitely have an effect on the health of the environment, which includes the community and other living beings. The objective of the research was to determine community behavior that resulted in environmental damage. The research used a descriptive quantitative method where the data collected was based on the results of a questionnaire using a simple random sampling technique. The results showed that the behavior of coastal communities was in the unfavorable category as it resulted in environmental damage to mangrove beaches. The conclusion of this study is that the behavior of the community is in the unfavorable category, causing environmental damage to the mangrove coast. This is supported by the overall results with the highest value category for population activity (50%), natural resource conditions (80%) and mangrove conditions (53.3%). ) is not very good. Keywords : Behavior, Coastal community, Environmental damage, Mangrove